MANAGEMENT OF PRODUCTION TO THE HORIZON OF FUNDS DEFINITIONS OF SPATIAL ORIENTATION MOBILE OBJECT - Sushchenko , O. A.; Kokhan , Yu. N.; Saifetdinov , R. A.; D.O. Voitkov, D. O. (Problems of Informatization and Management, 2021)
The features of algorithmic support of means for determining the spatial orientation of a moving object in the mode of bringing to the horizon are considered. Expressions for control and corrective moments are proposed.